Codesign of Digital Health Tools for Suicide Prevention: A Scoping Review - Wepa, Dianne; Neal, Martin; Abo-Gazala, Waseen; Cusworth, Sally; Hargan, Jae; Mistryh, Manoj; Vaughan, Jimmy; Giles, Stephen; Khan, Mehnaz (British Journal of Healthcare and Medical Research, 2023)
The importance of codesigning digital health tools for suicide prevention has gained popularity since 2012. Promoted as cost-effective and innovative, digital health tools are widely used but seldom described or evaluated from a codesign lens. This scoping review provides an overview of the research and gaps in the delivery of codesigned digital health tools for suicide prevention. This review is phase two within a three-phase study. Phase one involved a scoping review protocol which informed this scoping review and the results will contribute to a proof-of-concept project to develop a digital tool for suicide prevention (phase three). The search strategy followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-SCR) and Population, Concept, Context (PCC) framework to ensure reporting standards were maintained and supplemented by Arksey and O’Malley and Levac et al. The search for literature occurred from November 2022 to March 2023. Five data bases were searched: Medline, Scopus, CINAHL, PsycInfo and Cochrane Database of Systematic Reviews. Grey literature searches included government, non-government health websites, Google and Google Scholar. 3260 records were identified from the initial search and 61 were included in the final review. All members of the research team screened the included records. Data from published and grey literature were extracted and a narrative approach identified the results and five themes: acceptability by users, future inclusion of experts-by-experience, inconsistent use of Patient and Public Involvement (PPI), digital tools to supplement face-to-face therapy and digital divide. We found that none of the data from the included studies used codesign methodology and experts-by-experience roles were minimised as members of focus groups, advisory groups, pilot studies or at the final stage of usability testing. Future research is required where codesign involves co-authorship with experts-by experience, end-to-end partnership from design, implementation and evaluation of digital health tools for suicide prevention.